Soluble Organic Matter, its Biodegradation, Dynamics and Abiotic Production - Toosi, Ehsan Razavy (Oryx, 2010)
Soluble organic matter represent less than 1% of total soil organic matter (SOM) - but it contributes to many terrestrial ecosystem processes, due to its high mobility and reactivity in soil. Although it has been suggested that soluble organic matter (OM) may serve as an early indicator of soil quality changes as a result of shifts in land-use and management practices, only a few studies have addressed the dynamics of soluble OM in relation to land-use and specifically soil depth. This study focuses on two aspects of soluble OM. In the first part, I hypothesized that extractable OM obtained by aqueous solutions is a continuum of substances that depending on the extraction method can be separated into two operationally different fractions. The size and properties of these fractions may consistently differ among different land uses and at different soil depths. The objective of this part of the study was then to assess dynamics (size and properties, biodegradability and seasonality) of water extractable organic matter (WEOM) and salt extractable organic matter (SEOM) in a sequence of human dominated land-uses at topsoil and subsoil. At the second part of the study, I tested the regulatory gate hypothesis –abiotic solubilization of OM- as a primary controlling factor in soluble OM production. The objective of this study was to evaluate the impact of the microbial activity on the net production of dissolved organic matter (DOM) from the native SOM in the presence of added DOM and plant residue. For the first part of the experiment, the soil samples were collected from four land-uses under bog pine (Halocarpus bidwillii) woodland, tussock grassland (Festuca novae-zelandiae and Heiracium pilosella), cropland (Medicago sativa) and plantation forest (Pinus nigra). The selected land uses were located in the Mackenzie Basin, Canterbury, New Zealand and occurring on the same soils, topography and experienced similar climates. Soil samples were obtained from topsoil (0-20 cm) and subsoil (60-80 cm) at the end of each season ...